Quality Relationships between Superiors and Subordinates as Well as Fellow Colleagues at the Sweetener and Fiber Research Centre in 2010-2019 - Isni Tri Lestari; Maulina Pia Wulandari; Zulkarnain Nasution (International Journal of Science and Society, 2021)
Recurring organizational communication problems, lack of communication between superiors and subordinates, and also conflict at the employee level make the basis for researchers to conduct research and try to provide recommendations to improve conditions that occur in the Balittas organization. This study will focus on quality of relationships between superiors and subordinates as well as colleagues in organization. This study aims to describe and analyze the quality of the relationship between superiors and subordinates. This research was conducted using the Action Research method with the aim of being in Balittas from 2010 to 2019. Departing from the constructivism paradigm, this study carried out data collection by structured interviews and analyzed using the action research cycle from Coghland & Brannick. The quality of the relationship between superiors and subordinates, between colleagues for each period of each leader based on the LMX theory is dominated by the quality of the out group. This is because the relationship is only a contractual one. Subsequent research can develop the application of LMX theory in other government work units and create efforts to build quality in group relationships within Balittas. Based on LMX theory (low relationship quality) because the exchange of behavior of organizational members is limited to contractual ties and the low level of support and trust in each other.